Analisa Faktor Type Hedonic Shopping Motivation dan Faktor Pembentuk Kepuasan Tourist Shopper di Surabaya - Japarianto, Edwin (Jurnal Manajemen dan Kewirausahaan, 2010)
This research try to find factors in the hedonic motivation for the tourist shopper and satisfaction, researcher try to find factors can develop the basic motivation tourist shopper. Basic Hedonic motivation have six dimensions: Adventure Shopping, Social Shopping, Gratification Shopping, Idea Shopping, Role Shopping, and Value Shopping. Used 349 responden who collect from Judmental sampling and calculated by factor analysist. Reseracher find 5 hedonic motivation tourist shopper in Surabaya: Moody Shopper, Fashionable Shopper, Community Shopper, Price Sensitive Shopper and Charity Shopper. Satisfaction can analyst with 3 attributes, they are: attribute related to product, attribute related to service and attribute related to purchase, use the same correspondent and research tools. Researcher gets 4 variables to build satisfaction: Creative and uniqueness, excellent program and familiarity, Empathy and good performance, Equality cost & benefit managerial.